Achmea B.V. v. Slovak Republic (PCA). (June 2015) - Babiak, Otylia; Garel, Benjamin
Abstract : In Achmea B.V. v. Slovak Republic, an arbitration proceeding under the 1976 United Nations Commission on International Trade (UNCITRAL) Arbitration Rules, seated in Geneva, Switzerland, the Tribunal analyzed Achmea's claims under the Netherlands-Slovak Republic Bilateral Investment Treaty (BIT) and the Slovak Republic's objections that Achmea's claim manifestly lacked legal merit due to the inexistence of a "dispute" within the scope of the BIT. The Tribunal found that while an arbitrable "dispute" did exist between the parties, the claimant had not established a prima facie violation of the BIT, leading the Tribunal to decline jurisdiction.